Changes in the hydrophobic-hydrophilic properties of the organic matter of the chernozems of the Kamennaya Steppe - N. V. Matveeva; E. Yu. Milanovsky; O. B. Rogova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
Soil samples and physical size-density fractions isolated from them (silt particle size less than 1 µm, light fraction (LF) with a density of less than 2 g/cm3 and a fraction of the residue) of ordinary chernozem were studied in three contrasting variants of the experimental fields of the Kamennaya Steppe agrolandscape of the Voronezh region: mowed steppe, long-term permanent bare fallow and permanent corn – the main differences of which are in tillage (cultivated and not cultivated lands) and in the supply/absence of plant residues and root secretions. The LF content changes in the series: “mowed steppe” > “permanent corn” > “permanent bare fallow”, which corresponds to the direction of changes in the total carbon content of the soil and a decrease in the value of the contact angle of wetting (CA) of the surface of the solid phase of the studied chernozems. The determination of the total C and N content revealed the change in the qualitative and quantitative composition of the size-density fractions for different land use cases. Chromatographic fractionation of alkaline extractions of humus substances (HS) of chernozem samples and size-density fractions revealed an increase in the degree of hydrophilicity of HS while simultaneously increasing the hydrophobicity of the solid phase surface and the carbon content in the soil. HS of LF of the “mowed steppe” turned out to be by 63% more hydrophilic than HS of LF of “permanent bare fallow” and by 47% more hydrophilic than HS of LF of “permanent corn”. While the hydrophilicity of the HS silt differed by 16 and 27%, respectively. The hydrophilicity of the HS of the original soil in the plot of the “mowed steppe” was by 41% higher than the hydrophilicity of the HS in the soil in the plot of “permanent bare fallow” and by 24% higher than in the soil of the plot of “permanent corn”. In addition, changes in the hydrophilicity of HS of size-density fractions are more intense than the HS of the soil, so the change in the degree of hydrophilicity of HS of size-density fractions is an indicator of soil degradation under different agrogenic pressue.